Small Open Economy DSGE Model with Natural Disaster and Foreign Aid - Lim, Dickson A. (Animo Repository, 2017)
The Philippines is one of the countries in the ASEAN region to be regularly hit by natural disasters. In an analysis of natural disaster hotspots, the Philippines is one among several countries where large percentages of the population reside in disaster-prone areas (Hazard Management Unit of the World Bank, 2005). Consequently, these catastrophic events also entail adverse macroeconomic impacts to the economy (Bergeijk & Lazzaroni, 2015). Raddatz (2007) estimated that climate-related disasters reduce real GDP per capita by 0.6%. In the Philippines, Benson (1997) reported a reduction in GDP growth rate forecast by 3.3% following the Luzon earthquake in July 1990. In reality, the actual reported GDP growth rate in 1990 was even lower than the forecasted with an actual value of only 3.0%. Benson (1997) also noted that there was also a reported stagflation or an increase in both inflation and unemployment at 14% and 10.6%, respectively. A more recent joint study prepared by the Philippine government with the Asian Development Bank (ABD) and World Bank (WB) also reports a reduction in GDP growth rate forecast, an increase in government spending, and a decline of tax revenue collection following the tropical depression Ketsana (Ondoy) in 2009 (Post-Disaster Needs Assessment, 2010).